The Impact of Regulation 561/2006 on Fleet Management Viewed through Efficient Use of Drivers’ Working Time - Muha, Robert; Sever, Drago (Promet - Traffic&Transportation, 2009)
The introduction of contemporary procedures to fleet managementprocesses has recently changed the work planning andsupervision of driver’s work activities. Tendencies to control theimplementation of driver’s work have been present in modemprofessional practice for quite a long time; however, the equipmentavailable on the market limited its implementation. Theintensified development of digital tachographs has, in technicalterms, ensured such equipment considerably before the legislativegroundwork was prepared for its practical implementation.The Commission Regulation (EC) No. 561!2006 (implementationof Social legislation relating to Road Transport) does notbring any essential novelties in terms of permitted workload.Consistent monitoring of drivers activities, made possible bydigital tachographs, will have impact on the existing workingmethods. The topic of the present paper is in deep analysis ofthe impact of the mentioned regulation with special emphasison the conditions for the regulation of the current stage of driverswork and on the expected consequences. The essential imp011ancelies on the expected change in the mentality and approachto planning the driver’s activities in the transport processon the part of the ea n·ier: the outcome will eventually resultin the efficiency of each individual canier.